Literasi Komunikasi Wisata Desa Berbasis Teknologi Informasi: Studi di Desa Gondoruso Kecamatan Pasirian Kabupaten Lumajang - Moch. Choirul Arief; Pardianto Pardianto (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2022)
Rural tourism is an important aspect of developing the economy of rural communities. This study discusses how the village government and the community of Gondoruso, Pasirian District, Lumajang initiate rural tourism, including the way they propose a strategic plan to increase rural tourism through information technology-based communication literacy. The qualitative descriptive research approach was employed for data collection and analysis. The findings illustrate that, the initiative of stakeholders for the potential development of tourism in the village of Gondoruso to encourage the community's active role in order to comprehend the tourism potential through which the residents want to learn seriously about information technology which is currently developing rapidly. Besides, the local community also invite local governments to help prepare facilities and infrastructure. In regard with the strategic planning of an information technology-based village tourism communication literacy conducted through several steps; (1) forming Pokdarwis (a tourism awareness group). (2) Conduct information technology-based tourism literacy training for residents, especially youth. (3) Developing branding Gondoruso village tourism through online media both social media and websites.